The value of the universal progressive model in working with mothers and children in the primary care system - D.Kamalova (Zien Journals, 2023)
(PHC) institutions play an important role in child health and infant care. It is here that the population receives basic health services such as vaccinations, prenatal services, prevention and treatment of diseases.
Keywords: Health care; Primary health care